Systematic review of the cost-effectiveness of interventions in patients with multimorbidity - Phuc, Huynh Thien; Chi, Nguyen Pham Quynh; Giang, Tran Ngoc Truong; Thuy, Nguyen Thi Thu; Nhi, Vo Ngoc Yen (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Multimorbidity is becoming increasingly prevalent and has become a major challenge for healthcare systems. Conducting a systematic review of the cost-effectiveness of interventions in patients with multimorbidity is essential to support resource allocation decisions and optimize integrated care models. Objectives: A Systematic Review of the Cost-Effectiveness of Interventions in Patients with Multimorbidity. Materials and methods: The systematic review was conducted following PRISMA 2020 guidelines, with searches performed in PubMed, Cochrane, Embase, and Vietnamese health science journals up to October 31, 2025. Eligible studies were screened, quality-assessed using the CHEERS 2022 checklist, and all cost and ICER data were converted to 2024 USD. Results: The systematic review identified 21 articles with 20 primary studies, including 12 organizational and integrated care models, of which the majority (9/12 studies) reported cost-effective interventions. Reported costs ranged from savings of USD 3,393 to additional costs of USD 3,679, accompanied by improvements in QALYs from 0.007 to 0.298 compared with usual care. Five interventions focusing on behavior change, enhanced self-management, and digital health support showed considerable variation in costs, ranging from savings of USD 3,588 to additional costs of USD 287,946, and QALY changes from -0.030 to +0.031, with most ICER values falling below the willingness-to-pay threshold (4/5 studies). Three interventions evaluating rational medication use and optimization of treatment processes demonstrated that all included studies found these interventions to be dominant or cost-effective compared with their comparators (3/3 studies). Conclusion: The systematic review demonstrates the cost-effectiveness of interventions for patients with multimorbidity, providing an evidence base to inform the selection and implementation of future interventions in Vietnam.